Bottom‐up Synthesis of Water‐Soluble Gold Nanoparticles Stabilized by N‐Heterocyclic Carbenes: From Structural Characterization to Applications. Issue 56 (10th August 2022) - Thomas, Sophie R.; Yang, Wenjie; Morgan, David J.; Davies, Thomas E.; Li, Jiao Jiao; Fischer, Roland A.; Huang, Jun; Dimitratos, Nikolaos; Casini, Angela
Abstract: N‐heterocyclic carbenes (NHCs) have become attractive ligands for functionalizing gold nanoparticle surfaces with applications ranging from catalysis to biomedicine. Despite their great potential, NHC stabilized gold colloids (NHC@AuNPs) are still scarcely explored and further efforts should be conducted to improve their design and functionalization. Here, the 'bottom‐up' synthesis of two water‐soluble gold nanoparticles (AuNP‐1 and AuNP‐2 ) stabilized by hydrophilic mono‐ and bidentate NHC ligands is reported together with their characterization by various spectroscopic and analytical methods. The NPs showed key differences likely to be due to the selected NHC ligand systems. Transmission electron microscopy (TEM) images showed small quasi ‐spherical and faceted NHC@AuNPs of similar particle size (ca. 2.3–2.6 nm) and narrow particle size distribution, but the colloids featured different ratios of Au(I)/Au(0) by X‐ray photoelectron spectroscopy (XPS). Furthermore, the NHC@AuNPs were supported on titania and fully characterized. The new NPs were studied for their catalytic activity towards the reduction of nitrophenol substrates, the reduction of resazurin and for their photothermal efficiency. Initial results on their application in photothermal therapy (PTT) were obtained in human cancer cells in vitro. The aforementioned reactions represent important model reactions towards wastewater remediation, bioorthogonal transformations and cancer treatment. Abstract : Small water‐soluble N‐heterocyclic carbene‐stabilized gold nanoparticles (NHC@AuNPs) were synthesized via the bottom‐up approach and showed suitability for applications in catalysis and biomedicine.